The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1046/j.1475-1313.2002.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential vision testing – the relationship between visual acuity and Vernier acuity in the presence of simulated cataract

Abstract: To evaluate the utility of a computer controlled two-bar Vernier acuity measurement as a predictor of visual function in the presence of cataract we measured logMAR visual acuity and Vernier acuity in a group of 40 young normal observers under various levels of dioptric blur (0-3 D in dioptre steps). The Vernier thresholds were resistant to dioptric blur up to 2 D, but performance degraded with blur of 3 D for non-optimised Vernier stimulus parameters. The stimulus parameters, bar length and bar separation, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Myopic defocus (+1.00 DS) degraded distance HCVA by ~30% less than astigmatism, close to the power strength ratio (0.71) prediction . The spherical blur was less than that found in phakic eyes, possibly related to the extended depth‐of‐focus interval in pseudophakic eyes . For near vision, spherical refraction changes near VA by ~0.18 logMAR/DS compared with the ~0.10 logMAR/DC provided by the astigmatic refraction.The present data suggests that a pseudophakic eye with 1.00 DS of myopia will have better distance and approximately the same near VA as an astigmatic eye with 2.00 DC.…”
Section: Discussionsupporting
confidence: 61%
“…Myopic defocus (+1.00 DS) degraded distance HCVA by ~30% less than astigmatism, close to the power strength ratio (0.71) prediction . The spherical blur was less than that found in phakic eyes, possibly related to the extended depth‐of‐focus interval in pseudophakic eyes . For near vision, spherical refraction changes near VA by ~0.18 logMAR/DS compared with the ~0.10 logMAR/DC provided by the astigmatic refraction.The present data suggests that a pseudophakic eye with 1.00 DS of myopia will have better distance and approximately the same near VA as an astigmatic eye with 2.00 DC.…”
Section: Discussionsupporting
confidence: 61%
“…Quaid et al ( 2002 ) reported a correlation coefficient between Vernier acuity and optotype acuity of r = 0.8 for normal subjects. In our total population, we find that r = 0.52 ( p < 0.001); for our controls, we find r = 0.55 ( p = 0.0025); and for ASD, we find r = 0.57 ( p = 0.0057).…”
Section: Resultsmentioning
confidence: 99%
“…22 The effects of contrast reduction are greater on stereoacuity than on Vernier acuity. 20 Thus the differences we found between the stereoblind and stereoscopic subgroups could result from some optical degradation (perhaps refractive error, cataract, and/or deposits in the cornea) which was large enough to produce a differential effect on Landolt acuity and stereoacuity, but not large enough to affect Vernier acuity differentially. This notion is also supported by the correlation between Landolt acuity and stereoacuity in the stereoscopic patient subgroup.…”
Section: Correlationsmentioning
confidence: 74%
“…In contrast, our data from the Landolt test, showing greater impairment in the stereoblind subgroup, appear to be consistent with differences within the eyeball, either optical or retinal, between the two patient subgroups. For example, Quaid et al 20 showed that blurring with positive lenses or with contact lenses which simulate cataracts had a greater effect on letter than on Vernier acuity. In their study, blurring had little effect on Vernier acuity below two dioptres.…”
Section: Correlationsmentioning
confidence: 99%